Content-Language Integrated Learning in English Learning. Teacher Reflections - Jiménez-Benavides, Angela V. (2023)
In recent years, the use of Content and Language Integrated Learning (AICLE for is acronym in Spanish) has become very popular due to the concern of educating bilinguals to be competent for the demands of today's world. In Colombia, this approach has been widely adopted by bilingual schools. The objective of this article, which is part of a broader investigation on AICLE in the teaching of English, has as main reflection on the bibliographic objectives or scientific articles that contribute to the documentary corpus or state of the art of the investigation. In order to achieve the proposed objective, it was proposed as a qualitative research methodology with a review approach and documentary analysis of books, and scientific articles from databases such as Scielo, Redalyc and Dialnet, through the information systematization instrument in the Specialized Analytical Summary (RAE for its acronym in Spanish) done in Microsoft Excel software. The implementation of this strategy resulted in the compilation and analysis of 36 bibliographic sources that contributed to the research proposed through a reflection on the principles of the AICLE approach in the teaching of English.